HELMINTH FAUNA OF FISHES FROM THE UPPER PARANÁ RIVER FLOODPLAIN, BRAZIL - Massato Takemoto, Ricardo (2010)
The Paraná River is formed by junction of the Grande and Paranaíba Rivers and is the principal river of the La Plata basin. From source to mouth in the La Plata River estuary, the Paraná River flows for approximately 4,695 km (Petri & Fúlfaro, 1985) and drains most of South-Central South America. There are several dams in the main channel and tributaries of the Paraná River, but a floodplain still remains with a complex of tributaries, side channels, lakes, and marginal dikes (Stevaux, 1994; Souza Filho, 2009). This floodplain extends to the States of Paraná and Mato Grosso do Sul, encompassing areas of the Ilha Grande National Park, the Ivinheima State Park and the Environmental Protection Area (APA) of the islands and floodplain of the Paraná River